2020
DOI: 10.1002/fsn3.1588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different roasting methods on formation of acrylamide in pistachio

Abstract: Drying and roasting are conventional processes in the nut industry. However, roasting as an important procedure in nuts manufacturing may cause some physicochemical changes in nuts. Acrylamide is one of these chemical compounds that is formed due to the roasting process. Acrylamide is known as a neurotoxicant, carcinogen, and reproductive toxicant. In this study, raw and salted pistachios were roasted under three conditions including hot‐air, infrared (IR), and microwave methods. Then, 80 pistachio kernels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Various factors affect the reaction yields of acrylamide, such as heat processing method, heating temperature, heating time, concentrations and types of sugar compounds, and water content. This main effect of temperature and time in heat processing methods on acrylamide formation has been reported by many researchers [ 4 , 6 , 12 , 15 , 35 , 80 , 81 , 82 , 83 , 84 , 85 ]. Some studies indicate that microwave processing can facilitate Maillard reactions as with conventional heating methods.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 60%
See 4 more Smart Citations
“…Various factors affect the reaction yields of acrylamide, such as heat processing method, heating temperature, heating time, concentrations and types of sugar compounds, and water content. This main effect of temperature and time in heat processing methods on acrylamide formation has been reported by many researchers [ 4 , 6 , 12 , 15 , 35 , 80 , 81 , 82 , 83 , 84 , 85 ]. Some studies indicate that microwave processing can facilitate Maillard reactions as with conventional heating methods.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 60%
“…Elfaitouri et al [ 97 ] reported, that the increase of the power used during frying potato chips from 200 W to 800 W (with the temperature increase from 160 °C to 180 °C) increases the acrylamide content several times. Although they did not show such clear trends associated with duration of the frying process, the relationship of increasing acrylamide content with increasing the time of microwave food processing was confirmed by other authors [ 12 , 35 , 83 , 89 ]. Chen et al [ 90 ] reported that with the extension of the microwave heating time of shrimp chips from 40 s to 80 s, the acrylamide content increased almost 20 times (the process was carried out at 900 W).…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 75%
See 3 more Smart Citations